A Path to Balanced Budgets of Bund and Länder? The New Shape of the 'Debt Brake' and the 'Stability Council'. Issue 5 (19th October 2016) - Korioth, Stefan
ABSTRACT: This paper analyses the implementation of new debt rules and the function of the new Stabilitätsrat since its establishment in 2011. The new rules are explained and the effect of the new limit for public debt is examined. Furthermore, the composition, tasks and procedures of the Stabilitätsrat are described and evaluated. Finally, its activity is judged with individual examples. As a result, it is shown that for the new rules of Art. 109 para. 3, Art. 115 and Art. 143d GG to be successful, a normative commitment and corresponding political discipline not to incur new debts is required. The Stabilitätsrat alone is insufficient as an institutional framework to encourage budgetary discipline. Abolishing the Stabilitätsrat would be a first step in giving back control to politics in regard to debt and in dispelling the illusion that technocratic determination of the possibility to take new debt could end the debt problem.